Klasická sociologie Inocence A. Bláhy v kontextu soudobých diskusí - Dušan Janák (Historicka Sociologie, 2017)
The following text deals with the sociology of I. A. Bláha in the context of two contemporary discussions about values in social science: the first is a dispute about so called public sociology and the second represents feministic epistemological thinking. The author concludes we should distinguish between “public” and “engaged” sociology as two different ways of sociological entering to the public sphere. The public sociology is a wider concept which indicates the sociological entering to the public sphere and it doesn’t content evaluative approach necessary. The engaged sociology is dealing with something or someone and the evaluation of reality is its attribute. A confrontation of Bláha’s arguments with feminist epistemologies shows that the engaged social science impeaches the sharp barrier between facts and values and tries to interconnect factual and value judgments. From this point of view an evaluation bias a cognition and the cognition bias the evaluation. Although the interconnection of the evaluation and the cognition weaken the idea of infallibility or impartiality of scientific knowledge, on the other hand it weakens also the idea that, while delivering evaluative statements, we move in the sphere of absolute arbitrariness and irrational intuition and it boosts the idea that value biased discourse is possible as rational.